Sex hormone exposure and reproductive factors in pulmonary arterial hypertension: a case–control study. (February 2020) - Badlam, Jessica B.; Badesch, David; Brittain, Evan; Cordell, Shannon; Ding, Tan; Fox, Kelly; Hemnes, Anna; Loyd, James; Pugh, Meredith; Robbins, Ivan; Yu, Chang; Austin, Eric D.
Pulmonary arterial hypertension (PAH) is a sexually dimorphic disease that for unknown reasons affects women more than men. The role of estrogens, both endogenous and exogenous, and reproductive factors in this female susceptibility is still poorly understood. It has been strongly suggested that sex hormones may influence the development and progression of the disease. We sought to determine whether sex hormone exposures and reproductive factors associate with PAH patients compared to control subjects, using a questionnaire and interview to obtain information regarding these potential risk factors. We conducted a single-center unmatched case–control study. Six hundred and thirty-four women and men with PAH, as well as 27 subjects with BMPR2 mutations but no PAH and 132 healthy population controls were enrolled from the Vanderbilt Pulmonary Hypertension Research Cohort and researchmatch.org. Questionnaires and nurse-led interviews were conducted to obtain information regarding sex hormone exposures and reproductive factors. Additional history was obtained on enrolled patients including disease severity variables and comorbidities. Responses to the questionnaires were analyzed to describe these exposures in this population as well as assess the association between disease severity variables and sex hormone exposures. Reproductive and endogenous factors that determine lifelong estrogen exposure were similar between PAH cases and controls. Patients with associated PAH were significantly more likely to be postmenopausal compared to controls. There were similar rates of "ever-use" and duration of use of oral contraceptive pills and hormone replacement therapy in patients when compared to controls. Disease severity variables were not significantly affected by any exposure after adjusting for PAH sub-group. In contrast to our hypothesis, that a greater exposure to exogenous sources of female sex hormones associates with PAH case status, we found similar rates of endogenous and exogenous sex hormone exposure between PAH patients and unmatched controls.